Effect of neoadjuvant chemotherapy in patients undergoing radical cystectomy for muscle-invasive bladder cancer: a retrospective, multi-institutional study. (15th October 2019) - Nitta, Masahiro; Kuroda, Satoshi; Nagao, Kentaro; Higure, Taro; Zakoji, Hidenori; Miyakita, Hideshi; Usui, Yukio; Hasegawa, Masanori; Kawamura, Yoshiaki; Shoji, Sunao; Miyajima, Akira
Abstract: Objective: We evaluated the effect of neoadjuvant chemotherapy in patients undergoing radical cystectomy for urothelial bladder cancer. Methods: We retrospectively examined 140 consecutive patients with muscle-invasive bladder cancer (clinical stage T2 to T4 and N0) who underwent radical cystectomy with or without neoadjuvant chemotherapy at four academic institutions between January 2006 and December 2016. Patients were categorized into the neoadjuvant chemotherapy group (those who underwent treatment with any neoadjuvant chemotherapy regimen; n = 69) and the non-neoadjuvant chemotherapy group (those who did not receive any neoadjuvant chemotherapy regimen; n = 71). The primary outcome measure was overall survival. Results: The 5-year overall survival rates were 58.0% and 61.8% in the neoadjuvant chemotherapy and non-neoadjuvant chemotherapy groups, respectively ( P = 0.320). The 5-year overall survival rates for the neoadjuvant chemotherapy and non-neoadjuvant chemotherapy groups were 64.8% and 68.4%, respectively, among cT2N0 patients ( P = 0.688) and 38.6% and 21.6%, respectively, among cT3-4aN0 patients ( P = 0.290). When patients with cT3-4aN0 disease in the neoadjuvant chemotherapy group were divided into responders (<pT2) and non-responders (pT2-pT4), responders (<pT2) to neoadjuvant chemotherapy had a better 5-year overall survival rate (83.6%) than non-responders (pT2-pT4; 23.1%; P < 0.05); this was also observed in the non-neoadjuvant chemotherapy group (21.6%; P < 0.05). On multivariate analysis, the pathological T stage (<pT2 vs. ≥pT2) was a significant predictor of overall survival in the neoadjuvant chemotherapy group. Conclusion: Among cT3-4aN0 patients, survival outcomes were significantly better in responders (<pT2) to neoadjuvant chemotherapy than in non-responders (≥pT2) and in patients in the non-neoadjuvant chemotherapy group. Among patients with advanced stage disease (cT3 or 4), responders (<pT2) to neoadjuvant chemotherapy had a significant survival benefit. Abstract : Among patients with advanced stage disease (cT3 or 4 urothelial bladder cancer), responders (<pT2) to neoadjuvant chemotherapy had a significant survival benefit.